Membentuk Generasi Zakat Melalui Program Lab ZISWAF: Mahasiswa Asah Keterampilan Dalam Praktik Pengelolaan Zakat - Andriani, Andriani; Baitulloh, Sabit; Umam, Muhammad Khoirul; Khoiron, Muhammad Zidni; Yuanida, Nisia; Mudawamah, Dewi; Fauziyah, Siti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to analyze the programs of the Zakat, Infaq, Shodaqoh, and Waqf Laboratory (Lab ZISWAF) in forming a competent generation of zakat among students. This research is expected to provide an overview of how the younger generation today is not only struggling with theory, but is able to professionally develop the skills of managing zakat, infaq and sadaqah. The research method used in this study is field research with a qualitative approach. Data were collected through observation, interviews, and documentation of the academic community involved in the ZISWAF Lab program at FEBI IAIN Kediri. The results showed that the Ziswaf Lab program made a significant contribution in improving student skills in the practice of managing zakat, infaq, and alms, including febi berbagi, orphan compensation, and management of infaq-sadaqah funds. In addition, a special program for students of Zakat Management Practices (PPZ) also plays a role in fostering zakat awareness and philanthropic spirit among students, this is supported by the increase in knowledge about zakat and student understanding after participating in the program. The uniqueness of three different institutions is also the key for students to hone their skills, because each institution has its own characteristics in managing its philanthropic institutions.